The Operational Capacity of Turkish Intelligence within the Scope of Use of High-Technology Products - Daricili, Ali Burak (Seta Foundation, 2022)
This study evaluates the increasing operational capacity of the Turkish National Intelligence Organization (Milli Istihbarat Teskilati, MIT) within the scope of the high-technology products Turkiye has been developing, especially in the last 10 years. Turkiye's Unmanned Aerial Vehicle (UAV) program has made a significant contribution to MIT's operational power and to Turkiye's military capacity. MIT has effectively used armed and unarmed UAVs in counter-terrorism activities in Turkiye, Syria, and Iraq; it can obtain instant intelligence relating to terrorist targets and plan operational activities via effective Electronic Intelligence (ELINT) and Signal Intelligence (SIGINT) collection methods. The espionage provision that enables political decision-makers to make real-time decisions based on this intelligence plays a great role in determining Turkiye's regional policy strategies. Another hightech advance that contributes significantly to MIT's operational capacity is the Intelligence, Test, and Training ship, the Turkish Coast Guard (TCG) Ufuk, Turkiye's first national intelligence ship. As of January 2022, the use of the TCG Ufuk began to significantly increase MIT's technical intelligence capacity. This article analyzes the contribution of Turkiye's increasing capacity to develop high-tech products to the operational efficiency of Turkish intelligence, along with the intelligence cycle model followed by MIT within the scope of Turkiye's counter-terrorism and foreign espionage activities.
Keywords: Turkish National Intelligence Organization; ELINT; SIGINT; UAV; UCAV